1984
DOI: 10.1016/0035-9203(84)90028-2
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal variations in plasma retinol and carotenoid levels in rural Gambian women

Abstract: Plasma carotenoid levels exhibited a major seasonal variation in pregnant and lactating women in Keneba, a rural Gambian village. This is probably due mainly to the seasonally related contribution of mangoes, which are a major dietary component during May and June, but are essentially unavailable for the remainder of the year. Plasma retinol levels, on the other hand, exhibited much less seasonal variation, although a trend towards higher levels in May and June was just discernible. Plasma retinol levels were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

1997
1997
2011
2011

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 4 publications
1
12
0
Order By: Relevance
“…The study was carried out during the dry season and whatever coloured fruits and vegetables had been eaten in the previous week had been bought from the city, which is more than 110 km away from the Makhaza area. The seasonal non-availability of vitamin A and iron-containing foods has been documented in other African studies in Kenya and the Gambia (Bates et al, 1984;Kigutha et al, 1995). In view of recent observations that dark green leafy vegetables may not be as bioavailable as previously thought, (de Pee et al, 1995;1998a), the vitamin A intake in these women must be regarded as precarious.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…The study was carried out during the dry season and whatever coloured fruits and vegetables had been eaten in the previous week had been bought from the city, which is more than 110 km away from the Makhaza area. The seasonal non-availability of vitamin A and iron-containing foods has been documented in other African studies in Kenya and the Gambia (Bates et al, 1984;Kigutha et al, 1995). In view of recent observations that dark green leafy vegetables may not be as bioavailable as previously thought, (de Pee et al, 1995;1998a), the vitamin A intake in these women must be regarded as precarious.…”
Section: Discussionmentioning
confidence: 86%
“…It is little comfort and indeed misleading that many of our women had normal serum levels of retinol, since only ten of them had adequate stores of the vitamin as measured by RDR. The retinol levels are thus like a brittle facade that is likely to crack under the stress of breast-feeding and the seasonal inadequacy of vitamin supply in the community (Bates et al, 1984;Kigutha et al, 1995). Indeed, one of the lactating women never took part in the study because she proved to have Bitot's spots.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the adjusted prevalence of night blindness among pregnant women in some countries of WCAR is greater than the cut-off point of 5 % indicating that vitamin A deficiency is a public health problem in a population. In a study in rural Gambia, Bates et al (33) showed that women's plasma retinol levels are significantly lower than those observed in a group of pregnant and lactating women living in the UK. In addition, plasma retinol is significantly higher among pregnant and lactating Gambian women supplemented with 650 mg vitamin A daily (34) .…”
Section: Discussionmentioning
confidence: 91%
“…Seasonal patterns in reported fruit and vegetable intake or carotenoid intake occur in markedly different magnitudes by population, even after adjustment for age, body mass index, alcohol, smoking and other recognized covariates (Bates et al, 1984;Ziegler et al, 1987;Rautalahti et al, 1993;Olmedilla et al, 1994;Cooney et al, 1995;Forman et al, 1999). Seasonal effects are relatively strong in countries without extensive food preservation and transportation systems (Bates et al, 1984;Forman et al, 1999), and therefore access to carotenoid-rich foods may be season dependent. Economic diversity would also increase between-person variation (Willett, 1998) and day-to-day variation may be particularly large in developing countries if expensive carotenoid-rich foods are affordable occasionally.…”
Section: Discussionmentioning
confidence: 99%